DEVELOPMENT AND VALIDATION OF AN RP-HPLC METHOD FOR THE DETERMINATION OF ULIPRISTAL ACETATE IN BULK AND PHARMACEUTICAL DOSAGE FORM - SINGHA S, SANATHOIBA; RAO T, SREENIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This work makes an attempt to establish a sensitive and accurate method for the development and validation of an analytical method for estimation of ulipristal acetate (UPA) in bulk and pharmaceutical dosage form. Methods: A mixture of 20 mM acetate buffer pH 3.7 and methanol in the ratio of 70:30 (v/v %) was used as the mobile phase. An xBridge™ C18 column (250 mm × 4.6 mm, 5μ) was used for the analysis at a flow rate of 1 ml/min, injection volume of 20 μl, run time of 15 min, and detection wavelength of 309 nm. The repeatability (within-day in triplicates) and intermediate precision (for 2 days) were carried out by six injections and the obtained results within and between the days of trials were expressed as percent relative standard deviation (% RSD). The linearity of the method was determined by the analysis of analyte concentration across a range of 10 μg/ml–60 μg/ml. Results: The % RSD values of precision studies were found to be below the accepted limit of 2%. The method was found to be linear with a correlation coefficient (R2) of 0.98. The method was also found to be accurate and robust with suitable values. Limit of detection (LOD) and limit of quantification (LOQ) of the method were found to be 0.371 μg/ml and 1.23 μg/ml, respectively. Conclusion: The results of analysis prove that this method can be used for the routine determination of UPA in bulk drug and in pharmaceutical dosage forms.